Isaac Edward Kiev: Early Leader in American Judaica Librarianship - Stempler, Amy (Judaica Librarianship, 2011)
Isaac Edward Kiev (1905–1975), former Chief Librarian of New York’s Hebrew Union College-Jewish Institute of Religion, spent a lifetime facilitating Jewish research. This article, based on the author’s Master’s thesis on Kiev, focuses on his contributions to the founding of Jewish book and library organizations during the American post-war era, including the Association of Jewish Libraries, Jewish Book Council of America, Jewish Cultural Reconstruction, Inc., and numerous Jewish book foundations in the United States and Israel. In addition to providing insight into the creation of these associations, the article illustrates the parallel development of the fields of Judaica librarianship and Jewish Studies in academia. Kiev’s legacy continues into the twenty-first century through his lasting influence on his profession as well as the I. Edward Kiev Judaica Collection at the George Washington University.